Nucleon Momentum Distributions and Elastic Electron Scattering form Factors for 54Fe, 56Fe and 58Fe Isotopes - Abdullah, Ahmed N (Al-Nahrain Journal of Science, 2018)
The nucleon momentum distributions and elastic electron scattering form factors of the ground state for some 1f-2p shell nuclei, such as 54Fe, 56Fe and 58Fe isotopes, have been studied utilizing the Coherent Density Fluctuation Model formulated by means of the fluctuation function (weight function). The fluctuation function has been connected to the nucleon density distribution of the nuclei and obtained from the theory and experiment. The feature of the long-tail behavior at high momentum region of the nucleon momentum distributions has been determined by both the theoretical and experimental fluctuation functions. The calculated elastic electron scattering form factors for considered isotopes are in a good agreement with those of experimental data throughout all values of momentum transfer q.